A CLINICAL STUDY ON THE MANAGEMENT OF PAIN IN CAESAREAN SECTION PATIENTS WITH VRIHAT PANCHAMOOLA GHANASATWA - Rabi Narayan, Mahanta; Trilochanta, Mahanta; Ankit, Gupta; Payal, Gupta (International Journal of Ayurveda and Pharma Research, 2015)
The management of post operative patients is a multi dimensional approach of treatment. Many common problems are developed during post operative period. Pain is one of the biggest problems amongst them. Therefore, an effective pain control is very essential to manage pain for post operative patients. There are lots of analgesics available in modern medical science. But they are causing side effects to the patients. Considering above problems faced by patients, a potent, safe and effective analgesic and well known Vedanahara and Shoola prasamana drug Vrihat Panchamoola was selected for this study. In this study 50 lower segment caesarean section patients (L.S.C.S) registered from labour room of Prasutitantra Department, S.S. Hospital, I.M.S, B.H.U, Varanasi (U.P) were selected randomly and divided in two equal groups. Group-I as trial and Group-II as control group. The trial patients are given 1000mg (two capsules of 500mg each) Ghanasatwa of Vrihat Panchamoola twice daily and the control group patients have given 50 mg Diclofenac Sodium twice daily after operation when bowel sound onset. After comparative study it has been found that, the trial drug Vrihat Panchmoola Ghanasatwa has produced good analgesic response during post operative pain management of L.S.C.S, patients.